Characterization of ferucarbotran-loaded RBCs as long circulating magnetic contrast agents. (November 2016) - Antonelli, Antonella; Sfara, Carla; Weber, Oliver; Pison, Ulrich; Manuali, Elisabetta; Salamida, Sonia; Magnani, Mauro
Aim: The biomedical application of contrast agents based on superparamagnetic iron oxide nanoparticles is still limited because of their short intravascular half-life. The potential of red blood cells (RBCs) loaded with new ferucarbotran nanoparticles as magnetic contrast agents with longer blood retention time has been investigated.Materials & methods: Ferucarbotran was loaded into RBCs by a procedure of hypotonic dialysis and isotonic resealing. Ferucarbotran amounts encapsulated in RBCs were determined by NMR. The survival of ferucarbotran-loaded RBCs and bulk ferucarbotran was evaluated in the mouse bloodstream.Results: Blood retention time of these RBC constructs is longer (∼14 days) than the bulk ferucarbotran (∼1 h) with a slower Fe clearance from liver and spleen.Conclusion: Ferucarbotran-loaded RBCs could be used as potential contrasting agents for diagnostic applications in MRI/magnetic particle imaging.